Carbon molecular sieves from oil palm shell for separation of methane from carbon dioxide gas mixture - Herawan, Safarudin Gazali (2003)
Oil palm waste, the shells, have been utilized for the preparation of various microporous adsorbents with molecular sieving effect for gas adsorption and separation. Different processes like carbonization, CO2 activation and chemical treatments were applied to produce adsorbents with various pore sizes. Thedevelopment of ultramicroporosity has been observed in range 0.3 to 0.5 nm by the used of molecular probe analysis. All the adsorbents prepared have shown their capability in adsorbing CO2 and CH 4 but more selective towards CO2 . The study discovered that the char sample has shown the best molecular sieving effect for the separation of CO2 and CH4 where the selectivity value is the highest among the others.